Retrospective dose reconstruction for an incident involving a concealed radium needle. (December 2018) - Ekendahl, Daniela; Rubovič, Peter; Hupka, Ivan; Judas, Libor; Žlebčík, Pavel
Abstract: A historical radium ( 226 Ra) needle was found in a building in Prague. The needle was concealed in a wall under a window frame. Ambient dose equivalent rate measured in close proximity to the frame reached up to 2 mSv/h. The place was located between a corridor and a staircase where people normally did not stay; hence, any significant radiation exposure was not suspected. Because of a remarkable history of the building, our speculation was that the needle could have been concealed there during World War II. To verify this assumption, one adjacent brick nearest to the place of the find was removed. The brick was used for retrospective dosimetry based on optically stimulated luminescence (OSL) of quartz extracted from a chosen brick block. Dose rate values inside the brick block were determined by a laboratory reconstruction. The original exposure conditions were simulated using the needle and a brick wall containing thermoluminescence detectors (TLDs). We also performed a computational simulation with the Monte Carlo technique. The simulation provided us a more detailed dose rate distribution inside the brick block. Finally, we compared OSL quartz, TLD, and Monte Carlo results. A good agreement among the results supports the speculation that the radium needle was concealed during World War II. Highlights: A historical radium ( 226 Ra) needle was found in a wall. A brick was used for dose reconstruction based on optically stimulated luminescence (OSL) of quartz. Dose rate values inside the brick block were determined by a laboratory reconstruction with thermoluminescence detectors (TLDs). Dose distribution was calculated using the Monte Carlo technique. OSL, TLD, and Monte Carlo results were in a good agreement.